MORAL EDUCATION VALUE IN TEMBANG ILIR-ILIR LYRICS FOR THE SOCIETY (PRAGMATIC AND IMPLICATIVE STUDIES) - Sunarmi (International Journal of Social Science, 2021)
This study aimed to find the meaning or value of moral education implied in tembang ilir-ilir lyrics of Sunan Wali Sanga's (12th century) and its meaning for society. The narrative of the lyrics is expressed in Javanese. The study was carried out by using a qualitative paradigm, which was pursued by a single embedded descriptive case study. Data were collected from document / archive sources or libraries. Data validity used triangulation of data. Data were analyzed using pragmatic analysis models. The findings showed that moral education value in tembang Ilir-ilir lyrics was related to one's faith and piety to God. Faith and piety starts from the moment humans are born until they die. The manifestation of one's faith and piety in tembang Ilir-ilir lyrics expressed the need to believe in the oneness of God, doing shalat, and perform amar ma'ruf nahi mungkar (acts of virtue and stay away from God's prohibitions). The impact on readers was that they can understand the meaning and improve the belief of need to approach oneself towards God by carrying out worship according to what has been directed. The novelty of this study was namely delivering of da'wah that carried out by Islamic religious leaders by conveying the chanting of tembang which makes listeners feel entertained and happy, so that the message conveyed feels easy to accept and is motivated to be implemented.